2011
DOI: 10.1037/a0021322
|View full text |Cite
|
Sign up to set email alerts
|

Planning and articulation in incremental word production: Syllable-frequency effects in English.

Abstract: We investigated the role of syllables during speech planning in English by measuring syllable-frequency effects. So far, syllable-frequency effects in English have not been reported. English has poorly defined syllable boundaries, and thus the syllable might not function as a prominent unit in English speech production. Speakers produced either monosyllabic (Experiment 1) or disyllabic (Experiment 2-4) pseudowords as quickly as possible in response to symbolic cues. Monosyllabic targets consisted of either hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 72 publications
2
50
2
1
Order By: Relevance
“…Lexical access is assumed to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 consist of lexical selection and word-form encoding, which is further divided into morphological, phonological, and phonetic encoding (Levelt et al, 1999). All of these stages have been shown to be sensitive to frequency (e.g., Cholin, Dell, & Levelt, 2011;Jescheniak & Levelt, 1994;Piai, Roelofs, & van der Meij, 2012;Roelofs, 1998;Strijkers et al, 2010). Lexical access takes place between about 200 ms post picture-onset and about 145 ms before articulation onset (Indefrey, 2011;Indefrey & Levelt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lexical access is assumed to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 consist of lexical selection and word-form encoding, which is further divided into morphological, phonological, and phonetic encoding (Levelt et al, 1999). All of these stages have been shown to be sensitive to frequency (e.g., Cholin, Dell, & Levelt, 2011;Jescheniak & Levelt, 1994;Piai, Roelofs, & van der Meij, 2012;Roelofs, 1998;Strijkers et al, 2010). Lexical access takes place between about 200 ms post picture-onset and about 145 ms before articulation onset (Indefrey, 2011;Indefrey & Levelt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(1997) Memory andLanguage. 46, 57-84. doi: 10.1006/jmla.2001 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 where "grand" /gRã/ "avion" /avjõ/ is produced /grɑ.tavjɔ/) and picture 1.b illustrates a two-word phonologically neutral condition (grand livre-big book, /gRã.livR/).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many investigations converge on the span of encoding extending over the initial word, at least in adjectival noun-phrases with prenominal adjectives (Costa & Caramazza, 2002;Damian & Dumay, 2007;Dumay, Damian, Stadthagen-Gonzalez, & Perez, 2009;Schnur et al, 2006). At the interface with the phonetic level, some studies reported syllabic length effect in picture naming tasks with longer naming latencies for words of two syllables relative to one (Santiago, MacKay, Palma & Rho, 2000) and frequency effects for both the first and second syllable of a bisyllabic word (Cholin, Dell & Levelt, 2011) which suggests a span of encoding extending the initial syllable.…”
Section: The Span Of Encoding At the Phonological Levelmentioning
confidence: 99%
“…Intermediate, partially prosodified representations are stored in a phonological buffer until all segments are inserted. Once the word is prosodified, corresponding syllable motor plans are accessed, either by retrieving precompiled syllable-sized motor plans for frequent syllables or by assembling segment-sized motor plans for infrequent syllables (Cholin, Dell, & Levelt, 2011;Levelt & Wheeldon, 1994). Articulation may begin as soon as the first syllable motor plan is available (Meyer, Roelofs, & Levelt, 2003), or it may be delayed until all motor plans for the word are ready (Levelt & Wheeldon, 1994), in which case preceding motor plans are temporarily stored in an articulatory buffer (Meyer et al, 2003;Rogers & Storkel, 1999).…”
Section: Speech Planningmentioning
confidence: 99%